Three new species of African suckermouth catfishes, genus Chiloglanis (Siluriformes: Mochokidae), from the lower Malagarasi and Luiche rivers of western Tanzania - Friel, John P.; Vigliotta, Thomas R. (Zootaxa, 2011)
Recent fieldwork and review of existing collections containing Chiloglanis specimens from the lower Malagarasi and Luiche rivers in western Tanzania has revealed three new species that are readily distinguished from described congeners by external features. Two of the species, Chiloglanis igamba sp. nov., and Chiloglanis orthodontus sp. nov. are restricted to the Malagarasi basin. The third species, Chiloglanis kazumbei sp. nov., is more broadly distributed in both the Malagarasi and adjacent Luiche basin. A key to all described species within these two basins is presented, along with comments on the distribution and validity of nominal Chiloglanis species examined during this study.